Pangenomic analysis of Coxiella burnetii unveils new traits in genome architecture - Abou Abdallah, Rita; Million, Matthieu; Delerce, Jeremy; Anani, Hussein; Diop, Awa; Caputo, Aurelia; Zgheib, Rita; Rousset, Elodie; Sidi Boumedine, Karim; Raoult, Didier; Fournier, Pierre-Edouard (Frontiers in Microbiology, 2022)
Coxiella burnetii is the etiological agent of Q fever, a worldwide zoonosis able to cause large outbreaks. The disease is polymorphic. Symptomatic primary infection is named acute Q fever and is associated with hepatitis, pneumonia, fever, and auto-immune complications while persistent focalized infections, mainly endocarditis, and vascular infections, occur in a minority of patients but are potentially lethal. In order to evaluate the genomic features, genetic diversity, evolution, as well as genetic determinants of antibiotic resistance, pathogenicity, and ability to cause outbreaks of Q fever, we performed a pangenomic analysis and genomic comparison of 75 C. burnetii strains including 63 newly sequenced genomes. Our analysis demonstrated that C. burnetii has an open pangenome, unique genes being found in many strains. In addition, pathogenicity islands were detected in all genomes. In consequence C. burnetii has a high genomic plasticity, higher than that of other intracellular bacteria. The core- and pan-genomes are made of 1,211 and 4,501 genes, respectively (ratio 0.27). The core gene-based phylogenetic analysis matched that obtained from multi-spacer typing and the distribution of plasmid types. Genomic characteristics were associated to clinical and epidemiological features. Some genotypes were associated to specific clinical forms and countries. MST1 genotype strains were associated to acute Q fever. A significant association was also found between clinical forms and plasmids. Strains harboring the QpRS plasmid were never found in acute Q fever and were only associated to persistent focalized infections. The QpDV and QpH1 plasmids were associated to acute Q fever. In addition, the Guyanese strain CB175, the most virulent strain to date, exhibited a unique MST genotype, a distinct COG profile and an important variation in gene number that may explain its unique pathogenesis. Therefore, strain-specific factors play an important role in determining the epidemiological and clinical manifestations of Q fever alongside with host-specific factors (valvular and vascular defects notably).